The application of takaful in Eastern Pacific Industrial Corporaon (EPIC) in oil and gas industry among admin department. - Izudin, Irdina Safiah; Kamal, Asiah; Hasan , Nor Zuraida; Mustafa @ Busu, Zanirah (Journal of Islamic, Social, Economics and Development, 2025)
Safety and health at work are very important, particularly in sectors like the oil and gas industry. Heavy machinery and equipment, as well as risks and chemicals, are all present for workers in these industries. Insurance and takaful can lessen losses and shield employees from any mishaps. But a lot of individuals don't realize how important insurance and takaful are, which causes a lack of knowledge and comprehension. The purpose of this research paper is to examine the interview done at Eastern Pacific Industrial Corporation (EPIC) Oil & Gas Kemaman, as well as the knowledge of employees in the oil and gas sector regarding Takaful and its application. Workers in the oil and gas sector can safeguard their safety and prevent significant losses by being aware of the value of insurance and takaful. The application of Takaful and insurance in the Oil and Gas Industry at Eastern Pacific Industrial Corporation (EPIC) is the main topic of this research study. Its goal is to increase public knowledge of Takaful and insurance and its advantages within the sector. The necessity of employee backup insurance and takaful is discussed, along with the significance of insurance and takaful for business property and personal accidents. The report also emphasizes how crucial takaful and insurance is to safeguarding workers' safety in the sector and averting further losses.